2012
DOI: 10.1158/0008-5472.sabcs12-s3-7
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S3-7: Treatment with Histone Deacetylase Inhibitors Creates ‘BRCAness’ and Sensitizes Human Triple Negative Breast Cancer Cells to PARP Inhibitors and Cisplatin

Abstract: DNA damage induces DNA damage response (DDR), which regulates cell cycle transit, DNA repair and apoptosis. During DDR, stability and activity of ATR and CHK1 is essential for the cell cycle arrest and subsequent DNA repair through homologous recombination (HR) in which BRCA1 protein is involved. We have previously reported that ATR, CHK1 and BRCA1 are hsp90 client proteins and treatment with hsp90 inhibitor sensitizes cancer cells to DNA damage. We have also previously shown that treatment with pan-HDAC inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…proteins involved in HR repair of DSBs, BRCA1, and RAD51, were downregulated by both inhibitors. This is consistent with several studies that demonstrated HDAC inhibitors suppress HR gene expression through the E2F1 transcriptional regulator (17), translational repression via miRNAs such as miR182 (34), as well as posttranslational degradation through hyperacetylation of Hsp90 (35). Nonetheless, antineoplastic mechanism of action for HDAC inhibitors has not been well elucidated, and due to their broad range of possible targets, it is likely the SAHA may have affected the function of other proteins involved in DNA damage response.…”
Section: Discussionsupporting
confidence: 89%
“…proteins involved in HR repair of DSBs, BRCA1, and RAD51, were downregulated by both inhibitors. This is consistent with several studies that demonstrated HDAC inhibitors suppress HR gene expression through the E2F1 transcriptional regulator (17), translational repression via miRNAs such as miR182 (34), as well as posttranslational degradation through hyperacetylation of Hsp90 (35). Nonetheless, antineoplastic mechanism of action for HDAC inhibitors has not been well elucidated, and due to their broad range of possible targets, it is likely the SAHA may have affected the function of other proteins involved in DNA damage response.…”
Section: Discussionsupporting
confidence: 89%
“…In vitro studies have also demonstrated that HDAC inhibitor vorinostat and HSP90 inhibitor AUY922 were ranked near the top for inducing the HRD-like gene expression profiles in TNBC cell lines [118].Thus, treatment with HDAC inhibitors can increase the therapeutic efficacy of DNA-damaging agents, such as platinum compounds in TNBC. Indeed, in vitro studies show that cotreatment with a pan-HDAC inhibitor and cisplatin synergistically induced apoptosis of both BRCA1-mutant and BRCA1-proficient cell lines and HDAC inhibitor treatment induces synergistic lethality with PARPi and cisplatin in triple-negative breast cancer cell lines [119][120][121].…”
Section: Heat Shock Protein 90 and Histone Deacetylase Inhibitorsmentioning
confidence: 99%
“…Therefore, it is vital to understand the intrinsic DNA repair activity of each tumor type prior to DNA-damaging agent treatment. For instance, the deficient HR pathway in BRCA1/2-deficient breast or ovarian cancer creates a distinct vulnerability to PARP inhibitions (41,42). AML cells are more dependent than another tumor cells on NF-kB, and here, we clarified that NF-kB plays a critical role in DNA repair in AML cells (Figs.…”
Section: Discussionmentioning
confidence: 55%